2021
DOI: 10.1016/j.redox.2021.101880
|View full text |Cite
|
Sign up to set email alerts
|

The lipid peroxidation product EKODE exacerbates colonic inflammation and colon tumorigenesis

Abstract: Oxidative stress is emerging as an important contributor to the pathogenesis of colorectal cancer (CRC), however, the molecular mechanisms by which the disturbed redox balance regulates CRC development remain undefined. Using a liquid chromatography–tandem mass spectrometry-based lipidomics, we found that epoxyketooctadecenoic acid (EKODE), which is a lipid peroxidation product, was among the most dramatically increased lipid molecules in the colon of azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…In agreement with these studies, we showed that compared with control healthy mice, the AOM/DSS-induced CRC mice had a lower colonic expression of a series of anti-oxidative genes, such as Sod1 (encoding superoxide dismutase 1), Cat (encoding catalase), Gsr (encoding glutathione-disulfide reductase), Gsta1 (encoding glutathione S-transferase A1), Gstm1 (encoding glutathione S-transferase M1), and Hmox1 (encoding heme oxygenase-1), and had higher colonic expression of a pro-oxidative gene Mpo (encoding myeloperoxidase), demonstrating more severe redox stress in the colon tissues of AOM/DSS-induced CRC mice. Consistent with these findings in animal models, we found that, in the Cancer Genome Atlas (TCGA) database, the expressions of the anti-oxidant genes (CAT, GSR, GSTA1, GSTM1, and HMOX1) are reduced, while the expression of pro-oxidant gene MPO is increased, in the tumor samples of human CRC patients (Lei et al, 2021).…”
Section: Levels Of Ldes In Animal Models and Human Patients Of Ibd And Crcsupporting
confidence: 80%
See 4 more Smart Citations
“…In agreement with these studies, we showed that compared with control healthy mice, the AOM/DSS-induced CRC mice had a lower colonic expression of a series of anti-oxidative genes, such as Sod1 (encoding superoxide dismutase 1), Cat (encoding catalase), Gsr (encoding glutathione-disulfide reductase), Gsta1 (encoding glutathione S-transferase A1), Gstm1 (encoding glutathione S-transferase M1), and Hmox1 (encoding heme oxygenase-1), and had higher colonic expression of a pro-oxidative gene Mpo (encoding myeloperoxidase), demonstrating more severe redox stress in the colon tissues of AOM/DSS-induced CRC mice. Consistent with these findings in animal models, we found that, in the Cancer Genome Atlas (TCGA) database, the expressions of the anti-oxidant genes (CAT, GSR, GSTA1, GSTM1, and HMOX1) are reduced, while the expression of pro-oxidant gene MPO is increased, in the tumor samples of human CRC patients (Lei et al, 2021).…”
Section: Levels Of Ldes In Animal Models and Human Patients Of Ibd And Crcsupporting
confidence: 80%
“…We found that EKODE was significantly increased in the colon of the AOM/DSS-induced C57BL/6 mice compared with that of the healthy control mice. In addition, EKODE was also among the most dramatically increased fatty acid metabolites in the colon of the mice (Lei et al, 2021). The concentration of EKODE was not significantly increased in the plasma of AOM/DSS-induced CRC mice compared with the healthy control mice (Wang et al, 2019b), and this could be due to the low chemical and/or metabolic stability of EKODE in circulation.…”
Section: Levels Of Ldes In Animal Models and Human Patients Of Ibd And Crcmentioning
confidence: 91%
See 3 more Smart Citations